The L-shaped association between weight-adjusted-waist index and all-cause mortality in individuals with psoriasis: results from NHANES database retrospective cohort study - Chen, Jiawen; Zeng, Xueting; Xiang, Niu; Luo, Renwei; Xiao, Zhixun; Chen, Rongying; Lin, Beiqi; Ke, Hui; Gong, Ting; Ji, Chao (Frontiers in Immunology, 2025)
BackgroundWhile obesity is widely recognized as a robust risk factor contributing to both the onset and exacerbation of psoriasis—a chronic, immune-mediated skin disorder—the relationship between the Weight-Adjusted-Waist Index (WWI), an emerging metric for the nuanced evaluation of obesity, and mortality rates specifically within the psoriatic population is uncharted territory in current medical academic research. This study investigated the associations of WWI with all-cause mortality among American individuals with psoriasis.MethodsData from the National Health and Nutrition Examination Survey (2003-2004, 2005-2006, 2009-2010, 2011-2012, and 2013-2014). Death outcomes were determined by linkage to National Death Index (NDI) records through December 31, 2019. Cox proportional hazards model and the two-piecewise Cox proportional hazards model were used to elucidate the nonlinear relationship between WWI and all-cause mortality in psoriasis patients.ResultsA total of 577 participants were enrolled in the NHANES study, and 69 all-cause deaths occurred. After multivariable adjustment, higher WWI was significantly and nonlinearly associated with higher risk of all-cause mortality among participants with psoriasis. In addition, we found an L-shaped association between WWI and all-cause mortality, with WWI turning at 10.50cm/√kg for all-cause mortality. Among patients whose WWI was greater than the breakpoint, there was a 71% increase in the risk of death for each unit increase in WWI (HR 1.71; 95% CI 1.01, 2.88).ConclusionsNon-linear associations of WWI with all-cause mortality were observed in American patients with psoriasis, with a critical threshold of 10.50cm/√kg above which the risk of all-cause mortality increased significantly.